Phytochemical and neuroprotective evaluation of Citrus aurantium essential oil on cerebral ischemia and reperfusion (Bangladesh Journal of Pharmacology, 2018)
This study was conducted to investigate the neuroprotective effect of Citrus aurantium essential oil on hippocampal injury induced by transient global cerebral ischemia and reperfusion in rat. In total 50 rats were randomly assigned into five groups; control, sham, ischemia, and essential oil-treated (50 or 75 mg/kg) rats. Ischemia was induced by occlusion of the carotid artery for 30 min. Spatial memory, passive avoidance learning, anti-oxidant capacity, and lipid peroxidation during ischemia/reperfusion were evaluated. The compounds of the essential oil were analyzed by gas chromatography/mass spectrometry. Induction of ischemia/reperfusion caused a decline in learning and passive avoidance memory in rats.  C. aurantium exerted protective effects on the spatial memory, passive avoidance learning, anti-oxidant capacity, and lipid peroxidation during ischemia/reperfusion in animals. The main compounds of the  essential oil were camphor (45.9%), thymol (11.2%), linalool (6.6%), carvacrol (6.3%) and borneol (2.9%). The essential oil with anti-oxidant compounds significantly decreased the symptoms of ischemia/reperfusion injury.Video Clip of Methodology:6 min 58 sec   Click to watchShuttle box test: 2 min 51 sec   Click to watch3 min 21 sec   Click to watch2 min 31 sec   Click to watch2 min 15 sec   (withdrawn due to age restriction of the viewers policy)2 min 48 sec   Click to watch